IMF Research Bulletin, June 2008. (IMF Research Bulletin; IMF Research Bulletin, 2008)
IMF research summaries on Latin America's external linkages (by Shaun Roache) and on reaping the benefits of structural reforms (by Stephen Tokarick); regional study on the Eastern Caribbean Currency Union (by Paul Cashin and Evridiki Tsounta); listing of visiting scholars at the IMF during March-April 2008; listing of contents of Vol. 55 No. 2 of IMF Staff Papers; listing of recent IMF Working Papers; listing of recent external publications by IMF staff; and a call for papers for the Jacques Polak Ninth Annual Research Conference.